Manifestations of Familial Hemiplegic Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at University of Arkansas, Little Rock, AR report 3 cases of familial hemiplegic migraine complicated by reversible cerebral edema and followed by neurocognitive impairment.